Pengaruh Penerapan Sistem Informasi Akuntansi dan Kualitas Informasi Terhadap Kepuasan Klien Pengguna Jasa Akuntan - Fadilla, Fahmi; Samsiah, Siti (Forum Kerjasama Pendidikan Tinggi, 2025)
This study examines the extent to which the implementation of Accounting Information Systems (AIS) and information quality affect client satisfaction in the context of providing accounting services. The focus of this study is directed at clients of Candra Irawan Accounting Services Office, with a quantitative approach through the distribution of structured survey instruments to 37 active clients. The results of multiple regression analysis indicate that both the implementation of AIS and the quality of information have a positive and significant effect on client satisfaction, with significance values ??of 0.004 and 0.001, respectively. The regression coefficient of AIS implementation is 0.451, while the quality of information is 0.505, indicating that the quality of information has a more dominant influence. Simultaneously, both variables explain 60.6% of the variation in client satisfaction (Adjusted R² = 0.606), and the F test shows a significance value of 0.000. These findings confirm that the implementation of technology will not have a maximum impact without the availability of relevant, accurate, timely, and easy-to-understand financial information. This study contributes to the literature on technology-based accounting services and offers practical essence for accounting service providers in improving service effectiveness and client engagement through optimal information management systems and data quality.